Effects of overweight and smoking on aerobic capacity, autonomic and pulmonary function in physically inactive middle-aged male - Inthachai, Tharnwimol; Chondaen, Natchaya; Maiarin, Surinthorn; Kummungkun, Wannasiri; Chinda, Kroekkiat; Aroonprasertkul, Naphatsorn (Chulalongkorn Medical Journal, 2021)
Background: A higher body mass index (BMI) can lead to smoking, some people believe that smoking can help them to lose their weight and also quit smoking can cause weight gain. The effects of overweight and smoking have not been studied in physically inactive middle aged males, a vulnerable group in gaining weight and being at greater risk of developing cardiovascular diseases (CVD). Objective: This study aimed to determine the effects of overweight and smoking on aerobic capacity, autonomic and pulmonary function in physically inactive middle aged male subjects. Methods: Seventy-two physically inactive subjects were divided according to normal BMI nonsmokers (18.5 – 22.9 kg/m2 , n = 18), normal BMI smokers (n = 18), overweight BMI nonsmokers (23.0 - 24.9 kg/m2, n = 18) and overweight BMI smokers (n = 18). All subjects were measured for body composition, heart rate variability (HRV). Pulmonary function and maximal oxygen consumption (VO2max) were measured by spirometry and cycle ergometer, respectively. Normality in the data was tested by using the Kolmogorov Smirnov test. Two-way ANOVA was used to determine the effects of overweight BMI and smoking. Results: Overweight and smoking aggravated body composition imbalance, autonomic dysregulation and diminished VO2max. Overweight decreased force vital capacity (FVC), while smoking diminished forced expiratory volume in one second (FEV1), FEV1/FVC ratio and fat-free mass. This study also found interaction of visceral fat and low frequency (LF) value in physically inactive subjects. Conclusion: Overweight is as hazardous as regular smoking on VO2 max, pulmonary function. Overweight and smoking also decreased fat-free mass, increased visceral fat as well as autonomic dysfunction. It can be related tentatively to the development of CVD in physically inactive middle-aged males.